Short-Term Results of Preterm Infants and Comparison with the Recent International Network: Obtained from a Level III Neonatal Intensive Care Unit in Türkiye - Aslan Yılmaz; Nesrin Kaya; Zeynep Alp Ünkar; Kevser Sak; Yıldız Perk; Mehmet Vural (Cerrahpaşa Medical Journal)
Objective: This study aimed to evaluate the effects of developments in neonatal units over time by comparing the results of the last 15 years of our unit with recent reliable international data.